Use of Non Pharmacological Therapies for Pain Management in Children: A Survey of Pediatric Healthcare Provides - Marina Maffeo; Asia Bianchi; Beatrice Fogli; Veronica Meucci; Biagio Nicolosi; Daniele Ciofi (Infermieristica Journal)
Introduction. Pediatric pain management is a complex challenge, particularly in settings such as intensive care units and in postoperative care, where the use of analgesic drugs can result in significant side effects. The use of non-pharmacological therapies (NPTs) has been shown to be effective in reducing both pain and anxiety. Since they are safe and free of side effects, they are therefore suitable for reducing the adverse effects of pharmacotherapy and improving the compliance of pediatric patients.